The evaluation of loop mediated isothermal amplification (LAMP) for the detection of porphyromonas gingivalis using heat-treated saliva - Hanan, Rosnani Che AWang @ Abdul (Universiti Sains Malaysia, 2014)
Porphyromonas gingivalis has been implicated as a major pathogen of periodontitis. Thus far, there have been no reported studies on attempted to detect P. gingivalis by Loop Mediated Isothermal Amplification (LAMP) using heat-treated saliva. Therefore, this study aims to evaluate the applicability of LAMP assay for detection of P. gingivalis in heat-treated saliva samples. DNA of saliva samples from periodontitis patients and healthy subjects were prepared by using heat-treated method and commercial kits. The results obtained were then compared with those omit obtained by conventional PCR assay. In periodontitis patients, P. gingivalis was detected in 4/5 (80%) extracted DNA using commercial kit in both LAMP and PCR assays. Two out of five (40%) of heat-treated saliva of periodontis patients were positive by LAMP and none was detected by PCR assay. In healthy subjects, no sample was positive by PCR in both heat-treated saliva and extracted DNA using commercial kit. However, 2/5 (40%) of heat-treated saliva and 1/5 (20%) of extracted DNA using commercial kit were positive by LAMP assay. These findings suggested that LAMP assay was corresponded to those of conventional PCR when using extracted DNA prepared from commercial kit. However, LAMP assay using heat-treated saliva was more sensitive than the conventional PCR, suggesting the potential of LAMP assay using heat-treated saliva samples in detection of P. gingivalis.